Analisis Pengaturan terhadap Pertanggung Jawaban Pidana Penyelenggara Judi Online dalam Perspektif Hukum Positif dan Fiqih Jinayah - Rossy Annisa (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This research is motivated by the rampant practice of online gambling in Indonesia, which has had various negative impacts, both socially, economically, and morally, and the lack of comprehensive regulations regarding criminal liability for online gambling organizers. The purpose of this research is to determine how criminal liability for online gambling organizers is regulated under Indonesian positive law and to formulate ideal regulations for more effective law enforcement. The research method used is normative legal research, with a statutory and conceptual approach. Data was obtained through a library study of relevant laws and regulations, legal literature, and previous research findings. The results indicate that the criminal liability for online gambling organizers is regulated in the Criminal Code (KUHP), specifically Article 303 paragraph (1), Article 303 bis paragraph (1), and Article 303 paragraph (3). Furthermore, provisions regarding online gambling are also contained in Article 27 paragraph (2) in conjunction with Article 45 paragraph (2) of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE), as amended by Law Number 19 of 2016. However, these regulations are deemed inadequate to address the development of information technology-based crimes. Therefore, this study recommends the creation of special regulations regarding cybercrime that explicitly regulate online gambling crimes, including the forms of criminal liability for organizers, perpetrators, and participating parties. With these special regulations, it is hoped that law enforcement against online gambling crimes will be more effective and provide legal certainty.